Improvement Of Compressibility Of Gypseous Soil - nan, nan (Iraqi Journal of Civil Engineering, 2008)
The gypseous soils are distributed in many locations in Iraq. The Engineering properties of such soil will be changed when it is wetted and it leads to failure which causes danger on the structures built on. This reason needs to study its properties and to find the way to treat it. In this study, natural properties of soil prepared from Samarra-Salah al deen governorate were studied. The gypsum content of soil is about 32%. To improve this soil, many trials were carried out on the soil by additive of Portland cement and calcium chloride. For the importance of the compressibility of the soil, the effect of the additives were studied and it is found that addition of 3% of cement or 5% of calcium chloride will improve the soil compressibility.